2019
DOI: 10.1103/physrevlett.123.110502
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Error Correcting Codes in Eigenstates of Translation-Invariant Spin Chains

Abstract: Quantum error correction was invented to allow for fault-tolerant quantum computation. Systems with topological order turned out to give a natural physical realization of quantum error correcting codes (QECC) in their groundspaces. More recently, in the context of the AdS/CFT correspondence, it has been argued that eigenstates of CFTs with a holographic dual should also form QECCs.These two examples raise the question of how generally eigenstates of many-body models form quantum codes. In this work we establis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 39 publications
4
58
0
Order By: Relevance
“…Comparing (2.23) to (2.1), we arrive at the observation made in [8]: regions of finite energy density in the spectrum of theories that satisfy ETH form -correctable [[n, k, d]] approximate quantum error correcting codes with…”
Section: Eth As Aqeccmentioning
confidence: 75%
See 3 more Smart Citations
“…Comparing (2.23) to (2.1), we arrive at the observation made in [8]: regions of finite energy density in the spectrum of theories that satisfy ETH form -correctable [[n, k, d]] approximate quantum error correcting codes with…”
Section: Eth As Aqeccmentioning
confidence: 75%
“…In this work, we continue in this direction by studying the error correcting properties of CFTs in the AdS/CFT correspondence. More generally, we analyze the observation made in [8] that systems satisfying the eigenstate thermalization hypothesis (ETH) contain approximate error correcting codes in their spectrums. In doing so, we find a connection between generic chaotic theories, of which holographic CFTs are an example, and quantum error correction.…”
Section: Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…A first step towards showing the ubiquity of such features is the work of Brandao, et. al. [52]. There, it is shown that quantum chaotic systems satisfying the Eigenstate Thermalization Hypothesis (ETH) have energy eigenstates that form approximate quantum error-correcting codes.…”
mentioning
confidence: 99%